The Production and Characterization of Graphene Oxide - Unlu, N.; Canbay, C. Aksu (Amer Inst Physics, 2019)
Graphene varieties which have high -potential are fillers used to improve the properties of polymers. These materials are a layer of carbon atoms in an atomic thickness. It has been extensively studied in recent years due to its sp2 bond in hexagonal lattice, its structure in a two-dimensional single -atom thickness and its unusual electrical, thermal, mechanical properties and lightness. In this study, graphene oxide (GO) was synthesized from graphite using modified Hummers method. This method is simpler and less costly than other methods known in the literature. It is also a safer and more environment friendly method. Layered and very thin GO structures were observed in SEM images. In elemental analysis (EDX), the Oxygen (C)) content is approximately 21.27 %. This result shows us that oxidation process took place. In the X121) analysis, the peak of 20 was obtained as 11,239 . In addition, characteristic peaks of GO were observed on FT-IR. spectroscopy. It is understood from the results obtained that GO was synthesized successfully from graphite powder by modified Hummers method.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: Crystallization